DEIXIS IN "PETER PAN AND PETER PAN IN KENSINGTON GARDENS" NOVEL - Prichatin, Prichatin; Latifah, Latifah (Jurnal Ilmiah Humanika, 2020)
The objective of this research was to investigate or checked if five kinds of the deixis expressions found in the novel of ‘Peter Pan And Peter Pan In Kensington Gardens’ and what they refered to. This is an analytical research about deixis expressions in which a qualitative research was used as the method to collect and analyze the data. Deixis expression from 5 chapters of the novel were taken as the samples. The kind of data in this research was the deixis expression words related to person deixis, place deixis, discourse deixis, time deixis, and social deixis. The research found that mostly deixis expression words in the novel were personal deixis. There were lots of personal deixis expression words of one character in the novel that could become the reference of almost all personal deixis words.